Characteristics of initial deposition and behavior of radiocesium in forest ecosystems of different locations and species affected by the Fukushima Daiichi Nuclear Power Plant accident. (September 2016) - Komatsu, Masabumi; Kaneko, Shinji; Ohashi, Shinta; Kuroda, Katsushi; Sano, Tetsuya; Ikeda, Shigeto; Saito, Satoshi; Kiyono, Yoshiyuki; Tonosaki, Mario; Miura, Satoru; Akama, Akio; Kajimoto, Takuya; et al.
Abstract: After the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, information about stand-level spatial patterns of radiocesium initially deposited in the surrounding forests was essential for predicting the future dynamics of radiocesium and suggesting a management plan for contaminated forests. In the first summer (approximately 6 months after the accident), we separately estimated the amounts of radiocesium ( 134 Cs and 137 Cs; Bq m −2 ) in the major components (trees, organic layers, and soils) in forests of three sites with different contamination levels. For a Japanese cedar ( Cryptomeria japonica ) forest studied at each of the three sites, the radiocesium concentration greatly differed among the components, with the needle and organic layer having the highest concentrations. For these cedar forests, the proportion of the 137 Cs stock in the aboveground tree biomass varied from 22% to 44% of the total 137 Cs stock; it was 44% in highly contaminated sites (7.0 × 10 5 Bq m −2 ) but reduced to 22% in less contaminated sites (1.1 × 10 4 Bq m −2 ). In the intermediate contaminated site (5.0–5.8 × 10 4 Bq m −2 ), 34% of radiocesium was observed in the aboveground tree biomass of the Japanese cedar stand. However, this proportion was considerably smaller (18–19%) in the nearby mixed forests of the Japanese red pine ( Pinus densiflora ) and deciduous broad-leaved trees. Non-negligible amounts of 134 Cs and 137 Cs were detected in both the sapwood and heartwood of all the studied tree species. This finding suggested that the uptake or translocation of radiocesium had already started within 6 months after the accident. The belowground compartments were mostly present in the organic layer and the uppermost (0–5 cm deep) mineral soil layer at all the study sites. We discussed the initial transfer process of radiocesium deposited in the forest and inferred that the type of initial deposition (i.e., dry versus wet radiocesium deposition), the amount of rainfall after the accident, and the leaf biomass by the tree species may influence differences in the spatial pattern of radiocesium by study plots. The results of the present study and further studies of the spatial pattern of radiocesium are important for modeling future radiocesium distribution in contaminated forest ecosystems. Highlights: We estimated the amounts of radiocesium in five forests 6 months after the accident. The proportion of 137 Cs stock in the aboveground biomass varied from 18% to 44%. The initial spatial pattern of radiocesium is important for future modeling.